Dekonstruksi Stereotip Gender dalam Lagu Pop Arab “Ya Banat” yang Dipopulerkan Oleh Nancy Ajram - Mahyudin, Erta; Hanik Mahliatussikkah; Siti Jubaidah (Al-Ma‘rifah, 2025)
This article examines the deconstruction of gender stereotypes in Nancy Ajram's song “Yā Banāt” through the combined lens of critical discourse analysis and gender performativity theory. It explores how the song challenges entrenched stereotypes of Arab women by integrating cultural and religious symbolism with elements of cultural hybridity that bridge Arab tradition and global modernity. The research analyzes the song’s lyrics, the visual language of its music video, and audience responses on social media to reveal how “Yā Banāt”  articulates an active, joyful, and emancipatory identity for young Arab women. The study situates this work within the broader context of Arab feminist and popular culture discourses, addressing the gap in Arab music scholarship that often overlooks popular music as a site of gender negotiation. By incorporating theoretical frameworks from Islamic and Arab feminism as well as postcolonial studies, the findings highlight how popular music can function as a culturally resonant tool for social change, fostering new narratives of femininity that are both locally grounded and globally informed. This contributes to expanding feminist theory within the realm of popular culture in the Arab world.